Syi’ah Dalam Pembelajaran Pendidikan Agama Islam: Suatu Konten Analisis - Sri Mulyani; Lailatur Rohmah; Maimun (Kartika: Jurnal Studi Keislaman, 2026)
The Akidah Akhlak subject plays a crucial role in shaping religious understanding and character development of students in madrasah. One of the topics taught is Shi'ah as part of the discussion on schools of thought in Islamic theology (kalam). This study aims to analyze the content and presentation of Shi'ah material in the Akidah Akhlak textbook for Madrasah Aliyah and to examine its implementation in learning at MAN 2 Pamekasan. This research employs a descriptive qualitative approach with data collection techniques through in-depth interviews and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the Shi'ah material in the textbook has covered basic learning aspects, such as definition, historical emergence, the concept of imamah, and group classifications. However, the presentation of the material remains general, textual, and lacks contextual depth, with a dominance of the bayani epistemological approach, thus it has not been optimal in fostering students' critical thinking skills. The implementation of learning is carried out through lecture and group discussion methods with time constraints of only two to three meetings, resulting in students' understanding remaining at a basic level and not yet reaching in-depth analytical levels. This study recommends the need for developing more contextual, objective, and dialogical materials and learning strategies in Akidah Akhlak instruction